Shear stress-induced mitochondrial biogenesis decreases the release of microparticles from endothelial cells - Kim, Ji-Seok (Am J Physiol Heart Circ Physiol, 2015)
The concept of enhancing structural integrity of mitochondria has emerged as a novel therapeutic option for cardiovascular disease. Flow-induced increase in laminar shear stress is a potent physiological stimulant associated with exercise, which exerts atheroprotective effects in the vasculature. However, the effect of laminar shear stress on mitochondrial remodeling within the vascular endothelium and its related functional consequences remain largely unknown. Using in vitro and in vivo complementary studies, here, we report that aerobic exercise alleviates the release of endothelial microparticles in prehypertensive individuals and that these salutary effects are, in part, mediated by shear stress-induced mitochondrial biogenesis. Circulating levels of total (CD31(+)/CD42a(−)) and activated (CD62E(+)) microparticles released by endothelial cells were significantly decreased (∼40% for both) after a 6-mo supervised aerobic exercise training program in individuals with prehypertension. In cultured human endothelial cells, laminar shear stress reduced the release of endothelial microparticles, which was accompanied by an increase in mitochondrial biogenesis through a sirtuin 1 (SIRT1)-dependent mechanism. Resveratrol, a SIRT1 activator, treatment showed similar effects. SIRT1 knockdown using small-interfering RNA completely abolished the protective effect of shear stress. Disruption of mitochondrial integrity by either antimycin A or peroxisome proliferator-activated receptor-γ coactivator-1α small-interfering RNA significantly increased the number of total, and activated, released endothelial microparticles, and shear stress restored these back to basal levels. Collectively, these data demonstrate a critical role of endothelial mitochondrial integrity in preserving endothelial homeostasis. Moreover, prolonged laminar shear stress, which is systemically elevated during aerobic exercise in the vessel wall, mitigates endothelial dysfunction by promoting mitochondrial biogenesis.